Students’ Perception Of School Landscape And Its Influence On Learning Experience At Award-Winning Secondary Schools In Kelantan, Malaysia - Wan Abdul Rahman, Nik Roh Hayati (2008)
Many school grounds are designed to reflect only adult values and usages rather than the student’s needs. Yet, school landscape holds remarkable potential to support learning and providing plentiful of spaces, which offers various qualities and experiences. This study attempts to identify the characteristics of three schools landscape design, which had won the National Landscape Competition in Kelantan from 1999 to 2005, whether it has significantly influenced the student’s perception and learning experience. The selected schools are MRSM Pengkalan Chepa, SM Sains Tengku Mohammad Faris Petra, and SMK Kota. The general objective of the study is to acknowledge that school landscape is part of learning experience. Qualitative and quantitative methods are the research methodology of the study. The study is divided into two phases which are site observation and the correlational survey. The survey data was analyzed by using SPSS version 12. The study found that there is a significant positive relationship between the students’ perception of school landscape with learning experience. However, school landscapes of the selected three award-winning schools only influenced students’ perception and learning experience at moderate level. The results signified that students’ perception of school landscape and learning experience had been influenced by the characteristic of the school landscape and the activities that took place in it.